20(S)-Protopanaxatriol promotes the binding of P53 and DNA to regulate the antitumor network via multiomic analysis - Zhihua Wang; Wenbo Wu; Xiangchen Guan; Shuang Guo; Chaowen Li; Ruixue Niu; Jie Gao; Min Jiang; Liping Bai; Elaine Laihan Leung; Yuanyuan Hou; Zhihong Jiang; et al. (Elsevier, 2020)
Although the tumor suppressor P53 is known to regulate a broad network of signaling pathways, it is still unclear how certain drugs influence these P53 signaling networks. Here, we used a comprehensive single-cell multiomics view of the effects of ginsenosides on cancer cells. Transcriptome and proteome profiling revealed that the antitumor activity of ginsenosides is closely associated with P53 protein. A miRNA-proteome interaction network revealed that P53 controlled the transcription of at least 38 proteins, and proteome-metabolome profiling analysis revealed that P53 regulated proteins involved in nucleotide metabolism, amino acid metabolism and "Warburg effect". The results of integrative multiomics analysis revealed P53 protein as a potential key target that influences the anti-tumor activity of ginsenosides. Furthermore, by applying affinity mass spectrometry (MS) screening and surface plasmon resonance fragment library screening, we confirmed that 20(S)-protopanaxatriol directly targeted adjacent regions of the P53 DNA-binding pocket and promoted the stability of P53-DNA interactions, which further induced a series of omics changes.